Systemic and inhaled glucocorticosteroids in acute obstructive laryngotracheitis - O. V. Zaytseva (Медицинский совет, 2018)
Acute laryngotracheitis (croup) is an acute condition that most commonly affects children of the first 6 years. Croup is caused by viral infection of the upper airway, predominantly by parainfluenza virus. Croup is characterized by the signs of subglottic stenosis, which determines croup severity. Corticosteroids are the mainstay of croup treatment due to a strong anti-inflammatory effect. Typically, duration of corticosteroid treatment in croup does not exce ed several days. Even short-course systemic corticosteroids are associated with a number of adverse effects: nausea, vomiting, behavioral changes and sleep disturbance, etc. According to Russian clinical guidelines for croup management inhaled corticosteroid budesonide is the first line therapy. Budesonide efficacy in croup has been proved in numerous clinical trials. Based on similar effectiveness of inhaled and systemic corticosteroids in croup patients, budesonide is the preferred treatment option, because it helps to minimize the risk of adverse effects.